KAJIAN TERAPI KOMPREHENSIF DENGAN PENDEKATAN ERGONOMI TOTAL PADA PASIEN KANKER PAYUDARA DENGAN CANCER RELATED FATIGUE YANG KEMBALI BEKERJA - Nurhesti, Putu Oka Yuli; Adiatmika, I Putu Gede (Coping: Community of Publishing in Nursing, 2021)
A total ergonomic approach is needed to facilitate breast cancer patients who have been declared cured and return to work to be able to be comfortably and not lose productivity. Cancer Related Fatigue is one of the common symptoms that occur in patients with cancer. These symptoms are also experienced by cancer patients who receive chemotherapy, radiation therapy, bone marrow transplantation, or other cancer treatments. Patients who have recovered from cancer report that Cancer Related Fatigue is a symptom of the disorder that is experienced months or even years after cancer treatment ends. Fatigue that continues to occur in cancer patients can interfere with the patient's quality of life so that a good assessment and management of this condition is needed. The total ergonomics approach with a systemic, holistic, interdisciplinary and participatory approach through appropriate technology is made into a comprehensive therapy that combines physical activity, relaxation therapy and education is one of the most definitive forms of treating Cancer Related Fatigue. Keywords: Total Ergonomics Approach, Cancer Related Fatigue, back to work